2021
DOI: 10.2147/tcrm.s298147
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Impacted Lower Third Molar Extraction on Periodontal Tissue of the Adjacent Second Molar

Abstract: The extraction of impacted lower third molars (ILTM) is one of the most common procedures in oral-maxillofacial surgery. Being adjacent to lower second molars, most impacted lower third molars often lead to distal periodontal defects of adjacent second molars. Several symptoms may occur after extraction, such as periodontal pocket formation, loss of attachment, alveolar bone loss and even looseness of second molar resulting in extraction. The distal periodontal defects of second molars are affected by many fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 62 publications
0
14
0
Order By: Relevance
“…In the present study, out of 120 sites 13 sites exhibited ABD post-extraction distal to M2 and were found to be associated with mesioangular and horizontal IMP as more amount of bone is removed during the extraction. The surgical removal of a fully impacted tooth usually leaves a unilateral ABD due to the removal of partial buccal wall post extraction ( 4 , 32 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, out of 120 sites 13 sites exhibited ABD post-extraction distal to M2 and were found to be associated with mesioangular and horizontal IMP as more amount of bone is removed during the extraction. The surgical removal of a fully impacted tooth usually leaves a unilateral ABD due to the removal of partial buccal wall post extraction ( 4 , 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…One common indication for surgical extraction of M3, is the prevention and/or improvement of periodontal defects in adjacent second molar(M2) (2). Several previous studies have shown that fully erupted M2 that are in close proximity to impacted M3 showed greater prevalence of periodontal disease due to colonization by periodontal pathogens (3)(4)(5). Blakey et al (6) in a longitudinal study has shown that almost 25% of patients with retained and asymptomatic wisdom teeth had probing depths of at least 5 mm on the distal of the M2 and the mesial of the M3.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8] AO is one of the most prevalent post-surgical inflammatory complications following When patients complain of an excruciating extraction socket, researchers have found that they have AO when the socket is empty or the clot has dissolved, leaving denuded bone and a foul stench. 9,14,15 The current investigation, on the other hand, looked at the same postoperative symptoms on days three, five, and seven. The Rashid.…”
Section: Discussionmentioning
confidence: 99%
“…The accumulation of dental plaque plays integral role in causing oral diseases, including dental caries or inflammation of surrounding soft tissues, which result in pericoronitis, tooth and root resorption, and other periodontal diseases [10][11][12]. Impacted third molars also present an increased risk for cyst and tumour related with disorder of development process, such as dentigerous cyst, odontogenic keratocyst, ameloblastoma, and malignant tumours, including squamous cell carcinoma and odontogenic myxoma; although the incidence is very low [13].…”
Section: Id Idmentioning
confidence: 99%